PERAN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DALAM MEMBINA PESERTA DIDIK YANG PUTUS SEKOLAH (Studi Kasus di PKBM Mario Laha Kota Ternate Utara) - Rajaloa, Nani I; Umar, Sitirahia Hi; Yasim, Saira (Jurnal GeoCivic, 2023)
The research background of the Center for Community Learning Activities in Ternate City, especially in Akehuda village, is very important in order to help and provide space widely and freely to be used by the community ranging from the educated to those who have never studied the world of education. The research objectives are (1) To determine the role of the center for community learning activities (PKBM) in fostering students who have dropped out of school. (2) To find out the factors that influence PKBM in fostering students who have dropped out of school. (3) To find out what efforts the government has made towards PKBM Mario Laha to foster students who have dropped out of school.The research method used is qualitative descriptive research with a case study method. The subjects of this study are the head of PKBM, lurah, community leaders, and students. Observation, interview, and documentation data collection techniques.Ã‚Â  Based on the results of the study, it can be concluded that: (1) The role of the Mario Laha Community Learning Center (PKBM) is as a service provider in the form of package A, B and C programs. The presence of Mario Laha PKBM in Akehuda Village as an equality education institution makes students who drop out of school enthusiastic again to continue their education so that they get a diploma to continue their education to college or a career in the world of work. (2) ) Factors that can affect the Mario Laha Community Learning Activity Center (PKBM) include: 1) The number of out-of-school children in the Akehuda sub-district who work as motorcycle taxis. 2) The economic condition of Mario Laha PKBM students who are below the poverty line. 3) Negative opinions of peers and parents. 4) Online learning. (3) Efforts that have been made by the government towards Mario Laha PKBM to foster students who drop out of school are as follows.